Škola jako poskytovatel sociálních služeb - Hanzlíková, Jana (Univerzita Pardubice, 2008)
In the case of social services being provided by a school the experience shows particular specifics. Considering some of the services, these specifics can be qualified as mainly positive; however, considering the service of personal assistance, these specifics are disputable or even negative. They are mainly connected to target group definition, human resources, documentation development according to social services quality standards and they are the fundamental aspects of providing social services in the context of social services quality inspection.
Keywords: provider of social services; schools; specific provision of social services; personal assistance; socio-therapy workshop; continuity of services